2021
DOI: 10.3389/fncir.2021.791043
|View full text |Cite
|
Sign up to set email alerts
|

Differential Rearrangement of Excitatory Inputs to the Medial Prefrontal Cortex in Chronic Pain Models

Abstract: Chronic pain patients suffer a disrupted quality of life not only from the experience of pain itself, but also from comorbid symptoms such as depression, anxiety, cognitive impairment, and sleep disturbances. The heterogeneity of these symptoms support the idea of a major involvement of the cerebral cortex in the chronic pain condition. Accordingly, abundant evidence shows that in chronic pain the activity of the medial prefrontal cortex (mPFC), a brain region that is critical for executive function and workin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
30
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(32 citation statements)
references
References 82 publications
2
30
0
Order By: Relevance
“…These findings are consistent with emerging views that chronic pain is a disease in its own right [116, 92, 124], meaning that one systemic pathology underlies disparate types of pain. Our results help identify and characterize the genetic components of this pathology and suggest that brain prefrontal and affective/motivational circuits may play a key role, supporting converging evidence from animal [117, 54, 141, 41, 52] and human [8, 91, 62, 70] studies. Together, this evidence underscores the importance of new ways to diagnose and treat chronic pain, whereby a given chronic pain condition is not considered as only a symptom of a localized somatic disease but is seen as a manifestation of an underlying shared pathology with concurrent risk for other pain conditions and previously unexplored centralized treatment targets.…”
Section: Discussionsupporting
confidence: 75%
See 2 more Smart Citations
“…These findings are consistent with emerging views that chronic pain is a disease in its own right [116, 92, 124], meaning that one systemic pathology underlies disparate types of pain. Our results help identify and characterize the genetic components of this pathology and suggest that brain prefrontal and affective/motivational circuits may play a key role, supporting converging evidence from animal [117, 54, 141, 41, 52] and human [8, 91, 62, 70] studies. Together, this evidence underscores the importance of new ways to diagnose and treat chronic pain, whereby a given chronic pain condition is not considered as only a symptom of a localized somatic disease but is seen as a manifestation of an underlying shared pathology with concurrent risk for other pain conditions and previously unexplored centralized treatment targets.…”
Section: Discussionsupporting
confidence: 75%
“…There is converging evidence for the involvement of the nervous system: gene expression data shows an enrichment exclusively for brain tissues, and FUMA gene set analysis implicates biological processes specific to the nervous system. Echoing a recent report of heritability enrichment for chronic overlapping pain conditions exclusive to the CNS [59], these findings provide a genetic line of evidence for the reported alterations in brain circuitry shared by chronic pain conditions [116, 5, 62, 52]. In addition to CNS activity, however, the pathways mapped in FUMA implicate a broad range of other functions, such as gut development, locomotion, and protein secretion, suggesting that susceptibility to chronic pain may involve other systemic biological changes.…”
Section: Discussionmentioning
confidence: 66%
See 1 more Smart Citation
“…Latency (s) then sought to dissect the significance of NBM neuronal projections to the medial prefrontal cortex (mPFC), which represents a key hub in brain circuits underlying pain. The mPFC undergoes marked plasticity in several human clinical chronic pain conditions and particularly, a major focus has emerged on its deactivation observed in some chronic pain patients 15 , a finding that is also reported in animal models of neuropathic pain [16][17][18][19] . We therefore expressed ChR2-YFP in ChAT neurons of the NBM and placed the optic fiber for blue light illumination in the prelimbic cortex (PL), the mouse counterpart of the human mPFC (Fig.…”
Section: Dissecting the Contribution Of Nbm Cholinergic-gabaergic Pro...mentioning
confidence: 88%
“…In chronic pain, the activity of the medial prefrontal cortex (mPFC), a brain region critical for executive function and working memory, is severely impaired. The major extracortical sources of excitatory input to the mPFC come from the thalamus, the hippocampus, and the amygdala, which enables the mPFC to integrate multiple streams of information required for the cognitive control of pain, namely, sensory information, context, and emotional salience ( Jefferson et al, 2021 ). One study found that one night of total SD impaired descending pain pathways and sensitized peripheral pathways to cold and pressure pain ( Staffe et al, 2019 ).…”
Section: Introductionmentioning
confidence: 99%